Determination of Leading Sector Sukoharjo Regency: Location Quotient and Shift Share Esteban Marquillas Approach - Muhammad Raqib; Mohammad Rofiuddin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2018)
The purpose of understanding the development of economic sector in 2012-2016 in order to develop and manage the potential of the region in Sukoharjo. The method used to analyze the leading sectors in this research is location quotient and shiftshare analysis of Esteban Marquillas. The result of the research shows that there are eleven sectors which are the basic sector ie. Manufacturing sector, Electricity and Gas sector, Large and Retail Trade sector, Automobile and Motorcycle Reparation, Transportation and Storage sector, Accommodation and Food Service Activities sector, Information and Communication sector, Financial and Insurance Activities sector, Real Estate Activities sector, Business Activities sector, Human Health and Social Work Activities. Economic sectors are having a competitive advantage as well as specialization namely in the sectors of the Manufacturing; Wholesale and Retail Trade; Repair of Motor Vehicles and Motorcycles; Transportation and Storage; Information and Communication; Real Estate Activities; and Human Health and Social Work Activities. Sectors are having the highest three positive values are the sectors of Manufacturing; Wholesale and Retail Trade; Repair of Motor Vehicles and Motorcycles; and Information and Communication. Keywords : Development, Growth, Shift Share Estaban Marquillas